2020
DOI: 10.1177/0300060520973915
|View full text |Cite
|
Sign up to set email alerts
|

Complete retroperitoneal laparoscopic nephroureterectomy with bladder cuff excision for upper tract urothelial carcinoma without patient repositioning: a single-center experience

Abstract: Objective This study was performed to evaluate the outcome of complete retroperitoneal laparoscopic nephroureterectomy with bladder cuff excision (RLNU-BCE), which is performed to treat urothelial carcinomas in the renal pelvis or in the ureter higher than the crossing of the common iliac artery without patient repositioning. Methods We retrospectively analyzed the clinical data of 48 patients with upper tract urothelial carcinoma who underwent complete RLNU-BCE in our institution from May 2017 to September 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…The nephrectomy portion is thereby quite similar to that described by other groups utilizing retroperitoneal access for robot-assisted NU keeping in mind that none of these studies completed surgery under robotic assistance [4,12,13]. Compared to the transperitoneal approach which is currently the most common technique, we observed similar surgical characteristics with our technique.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The nephrectomy portion is thereby quite similar to that described by other groups utilizing retroperitoneal access for robot-assisted NU keeping in mind that none of these studies completed surgery under robotic assistance [4,12,13]. Compared to the transperitoneal approach which is currently the most common technique, we observed similar surgical characteristics with our technique.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, retroperitoneal approach might be preferential for patients with previous abdominal surgery to avoid intraperitoneal adhesions and occasionally time-consuming adhesiolysis [9]. To date, a number of studies described retroperitoneal access for robot-assisted NU, but none of these surgeries were completed under robotic assistance [4,12,13]. In the majority of cases management of the bladder cuff after robot-assisted retroperitoneal nephrectomy was only possible through intraoperative switch to either conventional laparoscopic surgery or even open surgery [4,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the CO 2 gas pressure during the laparoscopic procedure of LNU differs between institutions. In recent studies on LNU, laparoscopic procedures were performed with 10-14 mmHg CO 2 gas pressure [8,16,17]. It was suggested that a low CO 2 gas pressure of 8 mmHg in the present study might have in uenced the low IVR rates.…”
Section: Discussionmentioning
confidence: 75%
“…[35] Next, the television monitors and surgeons switch positions, and the distal ureter with the bladder cuff is transected within a complete retroperitoneal space. [13,36] While the efficacy and safety of CRNU have not yet been fully illustrated, some studies have suggested that it may offer certain advantages over other procedures. For example, Fang et al [19] found that CRNU resulted in significantly less estimated blood loss, a shorter duration of incision drainage tube, less time to ambulation out of bed, shorter postoperative hospital stay, and less time to oral intake compared to ONU.…”
Section: Discussionmentioning
confidence: 99%